2023
DOI: 10.25085/rsea.820103
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of three local isolates of entomopathogenic nematodes against the tomato leafminer, Tuta absoluta (Meyrick)

Abstract: The tomato leafminer, Tuta absoluta (Meyrick) a key pest of tomato both in greenhouses and open-fields, has spread rapidly throughout Iran. The efficiency of native isolates of three species of entomopathogenic nematodes (Steinernema feltiae, S. carpocapsae, Heterorhabditis bacteriophora) was evaluated against the tomato leafminer, T. absoluta larvae (outside leaf and inside galleries), and pupae at various concentrations and times in laboratory conditions. Experiments were conducted at 25 ± 2ºC, 65 ± 5% RH, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
1
0
0
Order By: Relevance
“…The present study showed differences in susceptibility to EPN between larvae and pupae, with larvae being the most susceptible stage. These results are consistent with Türköz and Kaşkavalci (2016) and Samie et al . (2023) .…”
Section: Discussionsupporting
confidence: 93%
“…The present study showed differences in susceptibility to EPN between larvae and pupae, with larvae being the most susceptible stage. These results are consistent with Türköz and Kaşkavalci (2016) and Samie et al . (2023) .…”
Section: Discussionsupporting
confidence: 93%